Comparative Study of School Inclusion Policy School for Students with Physical Disabilities in Three Brazilian Municipalities - Andrade, Emanuele Teixeira; Mendes, Enicéia Gonçalves (Education Policy Analysis Archives, 2015)
In recent years, the studies related to the efficiency and practices based on educational inclusion policies have shown controversial results. Besides that, studies are focused on singular experiences, and unable to evaluate in large-scale the impact of these educational policies in schools. The present study aimed to investigate and compare the barriers faced by the students with physical disabilities who are being educated in public schools in three different municipalities. The participants were 24 students with physical disabilities, aged from 7 to 16 years, who were enrolled in regular schools of three different municipalities (A, B, and C). For data collection, a set of interviews for the school context written by Scots, translated and adapted to Brazilian reality researchers was used. The results indicated variations in the number and types of barriers, according to the municipalities, and that in general the policies were well evaluated by these students with physical disabilities, considering the 16 indicators analyzed. However, there were notable differences among the three municipalities, and even in the better evaluated municipality, the qualitative analysis of the students reports allowed to identify and exemplify the remaining barriers. The importance is discussed for the school inclusion policy in making the systems responsible to advance removing of all the barriers identified by the students, and not just intervention in those that are more economically viable.